Pengenalan Budaya dalam Novel Entrok Karya Okky Madasari Bagi Pembelajar BIPA - Novita Herdiawati; Slamet Subiyantoro; Nugraheni Eko Wardani (BAHASTRA, 2020)
The Indonesian Language Program for Foreign Speakers (BIPA) in the learning process is inseparable from cultural material. In accordance with the achievements of learning aspects of culture into teaching material in the BIPA program. Culture must be introduced to BIPA learners to avoid culture shock because they will come into direct contact with Indonesian people with a variety of traditions, religions, and tribes. The purpose of this study is to analyze the cultural elements in the novel Entrok by Okky Madasari as a medium for cultural recognition for BIPA students. The object of research is focused on the Entrok novel by Okky Madasari. Data collection techniques through two events, namely literature review and reading. This research is a qualitative type with interactive analysis techniques. The results showed that there are seven cultural elements contained in the novel Entrok by Okky Madasari. The cultural elements consist of language, knowledge, equipment and technology, social organizations, livelihoods, religious systems and arts. Through these seven elements, Entrok's novel by Okky Madasari can be used as a medium of introduction to Javanese culture for BIPA learners at C1 and C2 levels. Learning using cultural aspects still emphasizes the principle of understanding language in communication.